THE 1245G/T POLYMORPHISMS IN THE COLLAGEN TYPE I ALPHA 1 (COL1A1) GENE IN POLISH SKIERS WITH ANTERIOR CRUCIATE LIGAMENT INJURY - Marta Stępień-Słodkowska; Krzysztof Ficek; Jerzy Eider; Agata Leońska-Duniec; Agnieszka Maciejewska-Karłowska; Marek Sawczuk; Aleksandra Zarębska; Zbigniew Jastrzębski; Agata Grenda; Katarzyna Kotarska; Paweł Cięszczyk (Termedia Publishing House, 2013)
Objectives: The aim of this study was to examine the association of 1245G/T polymorphisms in the COL1A1 gene with ACL ruptures in Polish male recreational skiers in a case-control study. Methods: A total of 138 male recreational skiers with surgically diagnosed primary ACL ruptures, all of whom qualified for ligament reconstruction, were recruited for this study. The control group comprised 183 apparently healthy male skiers with a comparable level of exposure to ACL injury, none of whom had any self-reported history of ligament or tendon injury. DNA samples extracted from the oral epithelial cells were genotyped for the 1245G/T polymorphisms using real-time PCR method. Results: Genotype distributions among cases and controls conformed to Hardy-Weinberg equilibrium (p=0.2469 and p=0.33, respectively). There was a significant difference in the genotype distribution between skiers and controls (p=0.045, Fisher's exact test). There was no statistical difference in allele distribution: OR 1.43 (0.91-2.25), p=0.101 (two-sided Fisher's exact test). Conclusions: The risk of ACL ruptures was around 1.43 times lower in carriers of a minor allele G as compared to carriers of the allele T.